Exploring the Experience of EFL Learners on a Website for Language Learning to Practice Speaking English - Asi, Natalina; Fauzi, Iwan; Lestari, Ariesta; Mardiana, Dina; Amalia, Novika (Institut Agama Islam Negeri Kudus, 2024)
In English language learning, web-based learning (WBL) provides a critical tool for practicing speaking skills, which requires synchronous interactions for effective learning. This study explores the efficacy of the